PENGARUH MODEL PEMBERDAYAAN BERPIKIR MELALUI PERTANYAAN TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA DI SMP NEGERI 10 KUPANG TAHUN AJARAN 2019/2020 - Novi Rosina Lingu; Fransina Th Nomleni; Theodora S.N Manu (Indigenous Biologi : Jurnal Pendidikan dan Sains Biologi, 2019)
ABSTRACT The main problem in this research was the lack of creative thinking ability of students class VIII SMP Negeri 10 Kupang. The purpose of the study was to determine the effect of thinking empowerment models through questions on student’s creative thinking abilities. The method used was an experimental method with a posttest-only control design. The population of all class VIII students wass 327 and the sample of class VIII H and class VIII J was 64 students. The sampling technique used was purposive sampling. Data collection was done by creative thinking tests. The data analysis techniques using t test with the help of SPSS version 19. The results showed that the ability to think creatively in the experimental class was higher, namely fluency of 89,45%, authenticity of 89,06%, detailing 82,03% and flexibility of 77,34% compared to creative thinking in the control class. Based on the results of the hypothesis test, the value of t count>t table / 12,597>1,99897 at the 5% significance level. It showed that there were differences in student’s creative thinking abilities between the experimental using PBMP learning models while the control class used lecture methods so that it can be concluded that there was a significant influence in the use of PBMP learning models on student’s thinking abilities.